Refugia as an Environmentally Friendly Plant for Increasing Production and Income of Corn Farmers - Meity Melani Mokoginta; Yurnaningsi Mohamad (Newinera Publisher, 2022)
The research was conducted at the Suka Maju Farmer Group, Molamahu Village, Pulubala District in March 2020. The research objective was to determine the types of Refugia plants, production yields and farmers' income. This research was traced using descriptive methods for the use of refugia plants and t test to analyze farmers' income. The results of the research on refugia plants were beneficial for farmers as natural enemies of pests and there was an increase in the income of the Suka Maju Farmer Group after using refugia as a natural enemy of pests. The yield of maize by farmers who apply refugia plants is higher (10.51 tonnes / ha) than those using conventional methods (6.67 tonnes / ha) and there is a difference in income between farmers using conventional methods and those applying refugia plants. The income yield of farmers using refugia plants was higher (Rp. 33,523,200) than those using conventional methods (Rp. 21,169,920).